Program Mentoring Teknik Ecoprint Berbasis Keanekaragaman Vegetasi Sebagai Produk Alternatif Cendera Mata Khas Desa Wisata Padusan Pacet Mojokerto - Putri, Dhika Maha; Nailul Insani; Grace Tjandra Leksana; Ronal Ridhoi (Journal of Islamic Economy and Community Engagement, 2025)
Padusan Village is one of the popular tourist destinations among tourists when they want to spend their holiday time, so Padusan Village can be called a Tourist Village. The development of Padusan Village into an area that has many tourist attractions has created new things in the community, one of which is the emergence of MSMEs around Padusan Village. However, the majority of MSMEs in Padusan Village only sell agricultural products and home-processed food. There are no MSME actors in Padusan Village who sell souvenir products which are the hallmark of Padusan Village. Some of the problems that occur in Padusan Village are the lack of understanding from the community regarding the importance of souvenirs as souvenir products in the tourism industry, in addition to the low ability of the Padusan Village community in making souvenirs. Based on the existing problems, the service team from the State University of Malang wants to carry out community service activities in the form of mentoring on ecoprint techniques based on vegetation diversity as an alternative product for souvenirs typical of Padusan Pacet Tourism Village, Mojokerto. This service activity is carried out to realize the community's abilities and skills in producing souvenir products typical of the Padusan Tourism Village so that Padusan Village as a tourist village can develop further and increase the economic income of Padusan Village. The partner problem solving method in this activity is in the form of training and mentoring activities which begin with providing theory, practice and evaluation of the participants' work. This service activity was carried out well and smoothly, all participants followed the sequence of events from start to finish. The result of this service activity is an increase in skills for the Padusan Village community in producing handicrafts using ecoprint techniques and has the potential to become a business opportunity in Padusan Village.